Taxation and distribution of income in Brazil: New evidence from personal income tax data - Sérgio Wulff Gobetti; Rodrigo Octávio Orair (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
This paper presents a critical analysis of income and profit taxes in Brazil, demonstrating how measures adopted in the 1980s and 1990s, as a result of mainstream recommendations, hindered the redistributive role of taxes in the country. Investigation of tax data reveals a high degree of income concentration at the top of the distribution, low progressivity and violations of the principles of horizontal and vertical equity. The main reason for these distortions is the complete tax exemption of dividends for shareholders, a benefit that is very rarely seen in developed countries. We propose a return to a progressivity-focused tax reform plan, a theme that has returned as a focus of debates with Piketty (2014).
Keywords: H24; N46; E62; 330; Income tax; Tax progressivity; Tax reform; Income distribution; Tax data